Surface characteristics of electrospun p-sulphonated calix[4]Arene functionalized cellulose acetate nanofiber and its behaviour towards methylene blue adsorption - Basri, Nur Amilah Fadlina; Wahid, Mohd Haniff; Zainal, Zulkarnain; Alang Ahmad, Shahrul Ainliah; Abdull Manap, Mohd Rashidi (Hindawi, 2022)
p-sulphonated calix[4]arene (p-SOCX) functionalized cellulose acetate/graphene oxide (CA/GO) nanofibers were successfully prepared via the electrospinning technique. The presence of p-SOCX within the fiber matrix was ascertained using Fourier Transform Infrared spectroscopy and Carbon-Hydrogen-Nitrogen-Sulphur elemental analyses. Apparent changes in morphology of the samples were observed under scanning electron microscope where fiber diameters increased with increasing p-SOCX content. Preliminary dye removal test at different pH, dosage, and temperature of functionalized CA/GO nanofiber demonstrates enhanced adsorption capacity of methylene blue in presence of p-SOCX compared to pristine CA nanofiber and CA/GO nanofiber at an optimum pH 8. The highest removal efficiency obtained was 88.84% with initial methylene blue dye concentration of 10 mg/L, adsorbent dosage of 20 mg/10 mL, contact time of 30 min at room temperature ca. 293 K.